Treatment nonadherence and neurocognitive impairment in bipolar disorder. - Martinez-Aran, A; Scott, J; Colom, F; Torrent, C; Tabares-Seisdedos, R; Daban, C; Leboyer, M; Henry, C; Goodwin, G; Gonzalez-Pinto, A; Cruz, N; Sanchez-Moreno, J; et al. (2009)
OBJECTIVE: Little is known regarding the relationship between treatment adherence and residual cognitive dysfunction in euthymic bipolar disorder patients. This study aimed to investigate whether poor treatment adherence is associated with cognitive impairment in euthymic bipolar patients and whether other factors may be associated with both adherence and cognitive functioning. METHOD: Euthymic DSM-IV bipolar I or II disorder patients (N = 103: 61 with high levels of treatment adherence and 42 with poor treatment adherence) were assessed using a neuropsychological battery targeting attention, psychomotor speed, verbal memory, and executive functions and compared with 35 healthy controls of similar age, sex distribution, and education. Data were collected from September 2005 to June 2007. RESULTS: Bipolar patients with poor treatment adherence had more hospitalizations than those with high adherence. After controlling for age, gender, estimated IQ score, and Young Mania Rating Scale and 17-item Hamilton Rating Scale for Depression scores, non-treatment-adherent patients performed less well than normal controls in verbal learning and some executive functions. Among treatment-adherent and poorly adherent bipolar disorder patients, performance was similar in attention tasks and short-term and long-term verbal recall, but non-treatment-adherent patients were more impaired in ability to inhibit interferences and in spatial working memory. Poorer treatment adherence also was associated with the bipolar I subtype and with greater illness severity, as indicated by number of manic episodes and hospitalizations and history of psychosis. Pharmacologic factors, such as treatment with lithium, may also influence the relationship between neurocognition and adherence. CONCLUSIONS: There is a close relationship between poor treatment adherence and cognitive impairment, but the causal inferences of these findings are uncertain. Poor treatment adherence may worsen the course of bipolar disorder and so indirectly worsen cognitive performance, or cognitive impairment may contribute to poor treatment adherence and reflect more severe illness.